MODERN TECHNOLOGIES FOR TEACHING STUDENTS THE SKILLS OF TECHNOLOGICAL THINKING (World Bulletin of Social Sciences, 2023)
Currently, teaching methods in modern conditions of education are going through a difficult period associated with the change of educational goals, the development of a new generation state educational standard based on a competence-based approach. It requires the search for innovative means, forms and methods of teaching and upbringing related to the development and implementation of modern educational and information technologies.